Chronic Viral Hepatitis in Human Immunodeficiency Virus-infected Patients - SİLİ, ULUHAN; KORTEN, VOLKAN (GALENOS YAYINCILIK, 2016)
Infectious diseases physicians taking care of human immunodeficiency virus-infected patients should investigate for the presence of chronic hepatitis caused by hepatitis B and hepatitis C virus infections. This is important as chronic viral hepatitis progresses more rapidly to end-stage liver disease in human immunodeficiency virus-infected patients. Once diagnosed, there are effective drugs for the treatment chronic viral hepatitis. Tenofovir containing anti-retroviral therapy effectively suppresses hepatitis B replication. Hepatitis C cure can be achieved with directly acting antiviral agents.
Keywords: Human immunodeficiency virus; chronic hepatitis B; chronic hepatitis C; co-infection; C VIRUS; B-VIRUS; HIV OUTPATIENT; COINFECTION; COHORT; DECOMPENSATION; METAANALYSIS; PREVALENCE; MORTALITY; HCV